2008
DOI: 10.1080/13693780701742399
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and antifungal susceptibility patterns ofSporothrix schenckiiisolates from a cat-transmitted epidemic of sporotrichosis in Rio de Janeiro, Brazil

Abstract: Since 1998 a cat-transmitted epidemic of sporotrichosis has been observed in Rio de Janeiro (RJ), Brazil. Besides the lymphocutaneous and fixed forms, other presentations, such as disseminated cutaneous and mucosal involvement, as well as for the first time, erythema nodosum and erythema multiforme have been reported associated with sporotrichosis. This study investigates the phenotypes and genotypes of Sporothrix schenckii isolates recovered from different clinical forms of the disease noted as part of this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…At present, no teleomorph is known for S. schenckii (de Beer et al 2003); however, we found, as with previous studies (Mesa-Arango et al 2002, O'Reilly & Altman 2006, Gutierrez-Galhardo et al 2008, some genetic variability in S. schenckii, especially when analysing strains from different countries. The band pattern of the US strain was totally different from those of Brazil, which is in accordance with results from other studies of S. schenckii, as well as with other pathogenic fungi, such as Paracoccidioides brasiliensis and Histoplasma capsulatum (Muniz et al 2001, Mesa-Arango et al 2002, Hahn et al 2003.…”
Section: Discussionsupporting
confidence: 35%
See 1 more Smart Citation
“…At present, no teleomorph is known for S. schenckii (de Beer et al 2003); however, we found, as with previous studies (Mesa-Arango et al 2002, O'Reilly & Altman 2006, Gutierrez-Galhardo et al 2008, some genetic variability in S. schenckii, especially when analysing strains from different countries. The band pattern of the US strain was totally different from those of Brazil, which is in accordance with results from other studies of S. schenckii, as well as with other pathogenic fungi, such as Paracoccidioides brasiliensis and Histoplasma capsulatum (Muniz et al 2001, Mesa-Arango et al 2002, Hahn et al 2003.…”
Section: Discussionsupporting
confidence: 35%
“…from the 1988 sporotrichosis epidemic in the United States (Cooper et al 1992). Recent molecular studies have assessed the genetic diversity of S. schenckii, demonstrating that different clusters of S. schenckii strains are related to different geographical origins (Marimon et al 2006, O'Reilly & Altman 2006, Gutierrez-Galhardo et al 2008. Moreover, Marimon et al (2007) proposed the existence of three new Sporothrix species through physiological and molecular studies.…”
mentioning
confidence: 99%
“…Strains from the sporotrichosis area of endemicity in Rio de Janeiro are more susceptible to itraconazole and terbinafine than strains from Spain or São Paulo, a neighbor state Rio de Janeiro in Brazil (90). Low terbinafine MIC values were described for strains from Venezuela, and high minimal fungicidal concentration values for posaconazole were found in Peruvian strains (235).…”
Section: Antifungal Susceptibility Testsmentioning
confidence: 99%
“…Although some strains can show resistance to this drug, geometric means commonly are low, ranging from 0.4 g/ml (9) to 4.08 g/ml (257). In general, despite the use of fluconazole as a therapeutic agent in some human and veterinary sporotrichosis cases (31,50), this antifungal does not inhibit S. schenckii growth in vitro (9,63,90,152,172,257). Some S. schenckii strains are susceptible to voriconazole in vitro, since MIC values of as low as 0.12 g/ml have been found (107); however, the high geometric mean MIC values, ranging from 6.50 g/ml (155) to 13.2 g/ml (152), suggest that most isolates are resistant in vitro to this drug.…”
Section: Antifungal Susceptibility Testsmentioning
confidence: 99%
“…The results show a high level of specificity (Sandhu et al, 1995). In past years, several molecular taxonomic studies using different methodologies, such as restriction fragment length polymorphism (RFLP) from different gene targets, random amplified polymorphic DNA (RAPD), DNA sequencing of internal transcriber spacer (ITS) regions of the ribosomal RNA (rRNA), PCR targeting the DNA topoisomerase II gene, amplified fragment length polymorphism (AFLP), and M13 PCR fingerprinting have demonstrated that Sporothrix schenckii isolates have different genetic characteristics, which suggests that they do not belong to the same species (Ishizaki et al, 2000;de Beer et al, 2003;Gutierrez-Galhardo et al, 2008;Kanbe et al, 2005;Mesa-Arango et al, 2002;Neyra et al, 2005;Reis et al, 2009;Watanabe et al, 2004;Zhang et al, 2006). In addition, Marimon and collaborators (2007) supported these findings by suggesting that, according to a combination of phenotypic and genetic features, S. schenckii should not be considered a single taxon that causes sporotrichosis in human and animals but should instead be considered a species complex that is comprised of at least four species: S. brasiliensis, S. globosa, S. luriei, and S. schenckii (Marimon et al, 2006(Marimon et al, , 2007(Marimon et al, , 2008.…”
Section: Molecular or Dna-basedmentioning
confidence: 99%